Crossing Numbers of Certain Graphs - Yiew, Yip Chong (2004)
Since Harary, Kainen and Schwenk conjectured in 1973 that the crossing number of the Cartesian product of an m-cycle with an n-cycle is for , many results on the crossing number of the Cartesian product of graphs have been obtained. In this thesis, we study and investigate the crossing numbers of and.